Keunggulan Kompetitif Berkelanjutan UMKM Zeze Juss Melalui Pendekatan Resource Based View (RBV) - Umi Larasati; Rasyidu Hayan Hidayat; Vicky F Sanjaya (Haka Vyza Media, 2025)
Many MSMEs in Indonesia have been affected by the COVID-19 pandemic, one of which is Zeze Juice, which was impacted by the pandemic in 2021. A study states that an SME can remain stable for approximately 4.5-5 years, while Zeze Juice, which was affected by the pandemic, managed to reestablish its business in less than 4,5 years and has now been operating for 8 months in the Sukarame area of Bandar Lampung. This study used a descriptive qualitative method by conducting interviews with informants. The results show that Zeze Juice applies the RBV theory, namely valuable, rare, inimitable, and non-substitutable. Zeze Juice has unique resources that are not easily imitated by competitors, which makes Zeze Juice highly sought after by customers, as can be seen from its high sales volume. Thus, it can be concluded that the use of strategic management, specifically the RBV theory, can help businesses excel in their field.